Patterns of better breast cancer care in countries with higher human development index and healthcare expenditure: Insights from GLOBOCAN 2020 - Azadnajafabad, Sina; Saeedi Moghaddam, Sahar; Mohammadi, Esmaeil; Delazar, Sina; Rashedi, Sina; Baradaran, Hamid Reza; Mansourian, Morteza (Frontiers in Public Health, 2023)
Background The huge burden of breast cancer (BC) necessitates the profound and accurate knowledge of the most recent cancer epidemiology and quality of care provided. We aimed to evaluate BC epidemiology and quality of care and examine the effects of socioeconomic development and healthcare expenditure on disparities in BC care. Methods The results from the GLOBOCAN 2020 study were utilized to extract data on female BC, including incidence and mortality numbers, crude rates, and age-standardized rates [age-standardized incidence rates (ASIRs) and age-standardized mortality rates (ASMRs)]. The mortality-to-incidence ratio (MIR) was calculated for different locations and socioeconomic stratifications to examine disparities in BC care, with higher values reflecting poor quality of care and vice versa. In both descriptive and analytic approaches, the human development index (HDI) and the proportion of current healthcare expenditure (CHE) to gross domestic product (CHE/GDP%) were used to evaluate the values of MIR. Results Globally, 2,261,419 (95% uncertainty interval (UI): 2,244,260–2,278,710) new cases of female BC were diagnosed in 2020, with a crude rate of 58.5/100,000 population, and caused 684,996 (675,493–694,633) deaths, with a crude rate of 17.7. The WHO region with the highest BC ASIR (69.7) was Europe, and the WHO region with the highest ASMR (19.1) was Africa. The very high HDI category had the highest BC ASIR (75.6), and low HDI areas had the highest ASMR (20.1). The overall calculated value of female BC MIR in 2020 was 0.30, with Africa having the highest value (0.48) and the low HDI category (0.53). A strong statistically significant inverse correlation was observed between the MIR and HDI values for countries/territories (Pearson's coefficient = −0.850, p-value < 0.001). A significant moderate inverse correlation was observed between the MIR and CHE/GDP values (Pearson's coefficient = −0.431, p-value < 0.001). Conclusions This study highlighted that MIR of BC was higher in less developed areas and less wealthy countries. MIR as an indicator of the quality of care showed that locations with higher healthcare expenditure had better BC care. More focused interventions in developing regions and in those with limited resources are needed to alleviate the burden of BC and resolve disparities in BC care.